EFFECT OF N, P ON GROWTH AND ARSENIC ACCUMULATION IN FERN Pteris vittata L. - Kim, Đặng Đình; Kim Anh, Bùi Thị; Trang, Phạm Thị Huyền (Vietnam Journal of Science and Technology, 2012)
SUMMARY More and more attention has been paid to the research on Phytoremediation and hyperaccumulators. Nowaday, the people concentrate in how to enhance the abilities of plants to accumulate more contaminants by addition of amending reagents. In this study, the pot experiments were conducted to understand the effect of N, P on Arsenic accumulation in Pteris vittata L.. Our study was undertaken to examine the effect of Phosphorus and Nitrogen on Arsenic accumulation in the As – Hyperaccumulator, as well as to verify the feasibility of Phosphorus and Nitrogen applied as fertilizer to increase the arsenic accumulation in Pteris vittata. The result showed that, Arsenic concentration in the frond is higher than that in the root of the fern. With the P added ≥ 400 ppm and N added 100 - 200 ppm, Arsenic accumulation in the fern were increased sharply. Obviously, Nitrogen and Phosphorus is also a potential accelerator for Phytoremediation of Arsenic contaminated soil.